Digital health interventions for people who use methamphetamine: a scoping review - Fletcher, Kathryn; Freestone, Jack; Clifford, Brendan; Ezard, Nadine; Kershaw, Stephanie; Acheson, Liam S.; Karavasilis, Theodora; Siefried, Krista J. (Frontiers in Psychiatry, 2026)
IntroductionMethamphetamine use is increasing and is associated with substantial health, social and economic harms. Despite these harms, many individuals delay or avoid treatment due to personal and systemic barriers. Digital health interventions (DHIs) are a promising avenue for expanding treatment access, however their application for methamphetamine use remains relatively underexplored. This scoping review aimed to identify and synthesise existing evidence on the feasibility, acceptability, and potential clinical impact of DHIs for people who use methamphetamine.MethodsFour databases (Embase, PubMed, PsychINFO, and Scopus) were searched up to December 18, 2024. Eligible peer-reviewed studies examined DHIs aimed at reducing methamphetamine use and reported outcomes related to feasibility, acceptability, engagement, or clinical outcomes. Data were extracted and synthesised descriptively.ResultsSeventeen records (from 15 studies) reporting on 1269 participants (aged ≥18) across six counties were included. Women were underrepresented (180/1,217; 14.8%) in studies reporting gender. Most participants (772/1269, 60.8%) met study inclusion criteria for methamphetamine use; the remainder (497/1269, 39.2%) met diagnostic criteria for methamphetamine use disorder. Thirteen unique DHIs were identified including web-based programs (n=2), text messaging (n=2), smartphone apps (n=6), chatbots or virtual agents (n=2), and virtual reality (n=1). Cognitive behavioural therapy approaches underpinned 8 of 13 (61.5%) interventions, and 8 of 15 studies (53.3%) used randomised controlled trial designs. Most DHIs were feasible and acceptable, with high satisfaction reported. Initial engagement was generally strong but declined over time; dropout rates ranged from 7.3% to 67.7%. Clinical impact was mixed. Some DHIs demonstrated reductions in methamphetamine use, craving or improvements in cognitive functioning and help-seeking, with some sub-groups appearing to benefit more than others.DiscussionDHIs show promise for people who use methamphetamine. While current evidence supports feasibility and acceptability, clinical outcomes are variable. High attrition and engagement challenges persist. Heterogeneity in study designs, measures, and reporting limits comparability. Future research should explore long-term outcomes, hybrid models, and co-designed approaches with a focus on gender and equity. With further development, DHIs may play a valuable role in the broader intervention landscape.